Pengaruh Motivasi dan Lingkungan Kerja Terhadap Kinerja Karyawan di PT. Bama Berita Sarana Televisi (BBSTV Surabaya) - Isnaini Diana Putri Abdullah (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2018)
PT Bama Berita Sarana Televsi (BBS TV Surabaya) is one of many companies that engaged in the field of entertainment and also one of many television companies which take place in Surabaya. There is problem founded about the low of employees work performance. This study aims to know and explain the effect of motivation and work environment either partially or simultaneously on job performance. This study is a quantitative study with 63 sample of PT Bama Berita Sarana Televisi (BBSTV Surabaya) employees, by using saturating sampling technique. The result of this study shows that (1) motivation partially has a negative significant effect on employees work performance, which t hitung is -4, 345 > t tabel 1,670 and the significant value is 0,000. (2) Work Environment partially has a positive significant effect on employees work performance, which t hitung is -2,687 > t tabel 1,670 and the significant value is 0,009. (2) Motivation and work environment simultaneously has an effect on employees work performance, which F hitung is 10,871 > F tabel 3,15 and the significant value is 0,000.